Serum level of (interleukin (IL)-2, IL-10, tumor necrosis factor (TNF)-α), motilin (MTL), gastrin (GAS), pepsinogen (PG), after Adjunctive Treatment in Patients with Chronic Atrophic Gastritis: Serum level of (interleukin (IL)-2, IL-10, tumor necrosis factor (TNF)-α), motilin (MTL), gastrin (GAS), pepsinogen (PG), - Xue, Pan (Journal of Medical Biochemistry, 2025)
Introduction: it was to demonstrate the impact of traditional Chinese medicine (TCM) matrine combined with omeprazole enteric-coated tablets on the gastric mucosal histopathology, gastric function, inflammatory cytokines, and Helicobacter pylori (H. pylori) eradication in patients with chronic atrophic gastritis (CAG). Materials and Methods: a retrospective collection of case data from 110 patients with CAG admitted to the TCM Department of the hospital was conducted. Patients were rolled into test group (TG, matrine + omeprazole enteric-coated tablets) and control group (CG, omeprazole enteric-coated tablets). The gastric mucosal histopathological scores, serological indicators (interleukin (IL)-2, IL-10, tumor necrosis factor (TNF)-α), gastric function (motilin (MTL), gastrin (GAS), pepsinogen (PG)), H. pylori eradication rate, and clinical efficacy were compared. Results: the degree of glandular atrophy, intestinal metaplasia, dysplasia, and inflammatory activity index in patients of TG post-treatment were lower than CG (P
Keywords: Serum level of (interleukin (IL)-2, IL-10, tumor necrosis factor (TNF)-α), motilin (MTL), gastrin (GAS), pepsinogen (PG), matrine; omeprazole enteric-coated tablets; chronic atrophic gastritis; Helicobacter pylori eradication rate; gastric mucosal histopathology